Virulence and transmission characteristics of clade 2.3.4.4b H5N6 subtype avian influenza viruses possessing different internal gene constellations - Wanchen Zhao; Xin Liu; Xinyu Zhang; Zhiwei Qiu; Jun Jiao; Yang Li; Ruyi Gao; Xiaoquan Wang; Jiao Hu; Xiaowen Liu; Shunlin Hu; Xinan Jiao; et al. (Virulence)
Clade 2.3.4.4 H5N6 avian influenza virus (AIV) has been predominant in poultry in China, and the circulating haemagglutinin (HA) gene has changed from clade 2.3.4.4h to clade 2.3.4.4b in recent years. In 2021, we isolated four H5N6 viruses from ducks during the routine surveillance of AIV in China. The whole-genome sequencing results demonstrated that the four isolates all belonged to the currently prevalent clade 2.3.4.4b but had different internal gene constellations, which could be divided into G1 and G2 genotypes. Specifically, G1 possessed H9-like PB2 and PB1 genes on the H5-like genetic backbone while G2 owned an H3-like PB1 gene and the H5-like remaining internal genes. By determining the characteristics of H5N6 viruses, including growth performance on different cells, plaque-formation ability, virus attachment ability, and pathogenicity and transmission in different animal models, we found that G1 strains were more conducive to replication in mammalian cells (MDCK and A549) and BALB/c mice than G2 strains. However, G2 strains were more advantageously replicated in avian cells (CEF and DF-1) and slightly more transmissible in waterfowls (mallards) than G1 strains. This study enriched the epidemiological data of H5 subtype AIV to further understand its dynamic evolution, and laid the foundation for further research on the mechanism of low pathogenic AIV internal genes in generating novel H5 subtype reassortants.